PENGEMBANGAN MODIG (MODUL DIGITAL) BERBASIS PEMBELAJARAN KONTEKSTUAL PADA MATERI PROSES PERUBAHAN BENTUK ENERGI KELAS IV SDN MANGGIS 2 PUNCU - Sri Indra Puspito Sari; Frans Aditia Wiguna; Rian Damariswara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research and development is to determine the validity, practicality, and effectiveness of Modig (Digital Module) Based on Contextual Learning on the Material of Energy Transformation Process for Grade IV of SDN Manggis 2 Puncu. Development) with the ADDIE model which consists of 5 stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subjects of this study were teachers and 33 grade IV students of SDN Manggis 2 Puncu. The data analysis techniques used were qualitative descriptive analysis and quantitative descriptive analysis. The results of this study indicate that (1) The validity test obtained a material validation score of 96% and a teaching material validation of 84%. The values obtained are included in the very valid category. (2) the practicality test obtained a teacher practicality score of 98%. The student practicality of the limited trial was 88% and the broad trial was 90%. The teacher's and student's practicality scores were then accumulated, resulting in a score of 93.5%. (3) The effectiveness test obtained a limited trial score of 87.5% and a broad trial score of 85.6%, categorizing it as highly effective. It can be concluded that the contextual learning-based digital module for the material on energy transformation processes for fourth graders at SDN Manggis 2 Puncu is highly valid, highly practical, and highly effective for use in classroom learning.